Tri Lulu: Community Resistance to Source-Based Waste Management Policies in Badung Regency Bali - Anak Agung Gede Agung Dalem; Anak Agung Ngurah Anom Kumbara; Nanang Sutrisno; Maria Matildis Banda (Pusat Kajian Bali Universitas Udayana, 2024)
Bali encounters a waste emergency due to the amplification in the type and volume of the population’s waste. The Bali government has initiated community resistance, particularly in Badung Regency, Bali. This study aims to critically reflect on this circumstance from the lens of the qualitative method using a cultural studies approach. Field research was performed by implementing the critical ethnography model. The study reveals that community resistance is categorized into three waste management dimensions called Tri Lulu, i.e., individual and public resistance, hyperregulation conflict, and disruption of local concepts. Individual and public resistance, both open and covert, reflects the failure of dialogue between subjective awareness and regulative practice in finding practical solutions. Hyperregulation in waste management causes policies to overlap and triggers conflicts of interest. Local concepts are disrupted due to increasing pressure on demographic and economic infrastructure. Pentahelix synergy is required to implement waste management policies in Bali.